Adopting The Endangered Species Act (ESA)â€ To Protect The Vulnerable Kelik Fish (Encheloclarias Tapeinopterus, Bleeker 1853) - Putri Kenanga; Yulia Rahman; Tiara Na Fasha; Rissal Muhemin; Pakih Rizki Romadhoni; Muhammad Syaiful Anwar (Journal of Aquatropica Asia, 2023)
Encheloclarias tapeinopterus is an endemic catfish found only from Bangka Island, Indonesia. This species is listed as a Vulnerable species based on the IUCN Red List, which means that the population of this species has decreased drastically over time, and it is possible that this species will become extinct in the near future if there are no efforts to save the species. Until now, there have been no reports regarding domestication and conservation efforts for this species. In addition, there has been no socialization and punishment given to people who catch this species. Society can freely catch E. tapeinopterus without any punishment or deterrent effect. Theoretically, Indonesia actually has a Conservation Law, namely Law Number 5 of 1990 concerning Conservation of Biodiversity and Its Ecosystems which provides protection for biodiversity. However, this law talks more about the conservation system than providing legal protection for wild animals and their habitats. Based on this, the legal protection of wild animals in Indonesia needs to be improved. In this article, we describe legal certainty if Indonesia can adopt the American Wildlife Protection law "The Endangered Species Act (Esa)" in the framework of efforts to protect the endemic fish Encheloclarias Tapeinopterus which has a vulnerable status. In this paper we compare Law Number 5 of 1990 and The Endangered Species Act law.